Deformation of orthotropic porous elastic bars under lateral loading - Ieșan, D. (Archives of Mechanics, 2010)
The present paper is concerned with the linear theory of inhomogeneous and orthotropic, porous elastic cylinders. The work is motivated by the recent interest in using of orthotropic porous elastic solid as a model for bones and for various engineering materials. A generalization of Saint–Venant’s problem to the case when the cylinder is subjected to body forces and to surface forces on the lateral boundary. The three-dimensional problem is reduced to the study of plane problems. The method is applied to investigate the deformation of a uniformly loaded circular cylinder.